درجة تواجد العنف المدرسي لدى طلبة المرحلة الثانوية في محافظة اللاذقية من وجهة نظر المدرسين فيها - أسعد شذا عبد الكريم (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
هدف البحث إلى تعرف آراء مدرسي التعليم الثانوي العام في محافظة اللاذقية حول درجة تواجد ظاهرة العنف المدرسي في مدارسهم، وكذلك تعرف الفروق في آرائهم تبعاً لمتغيرات (جنس المدرس، ومكان المدرسة، وسنوات الخبرة، والمؤهل العلمي والتربوي). اشتملت العينة على (136) مدرساً ومدرسة في التعليم الثانوي العام للعام الدراسي 2013/2014. ولتحقيق هدف البحث صممت استبانة تضمنت (حجم مشكلة العنف المدرسي، وأنواع العنف المدرسي، ومدى حدوث السلوك العنيف). ومن ثم عرضت الاستبانة على مجموعة مؤلفة من (9) محكمين في جامعتي دمشق وتشرين. وتم التأكد من ثباتها بتطبيقها على عينة شملت (30) مدرساً ومدرسة، من خلال حساب معامل ألفا كرونباخ، إذ بلغت قيمته (0.91). وبيّنت النتائج أن حجم مشكلة العنف المدرسي متوسطة. كما أوضحت النتائج أن أكثر أنواع العنف المدرسي انتشاراً هو العنف ضد الممتلكات، تبعها عنف الطلبة ضد الطلبة وعنف المدرسين ضد الطلبة. كذلك أظهرت أن درجة حدوث سلوك العنف في المدرسة كثير جاءت بنسبة (30.45%)، ودرجة حدوثه قليلاً جاء بنسبة (46.02%)، في حين أنه نادر الحدوث جاء بنسبة (23.52%). كما أظهرت النتائج عدم وجود فروق دالة بين آراء مدرسي المرحلة الثانوية في محافظة اللاذقية حول درجة تواجد ظاهرة العنف المدرسي تبعاً لمتغير (جنس المدرس، ومكان المدرسة)، ووجود فروق دالة تبعاً لمتغيرات (عدد سنوات الخبرة، والمؤهل العلمي والتربوي للمدرس)، وقدم البحث عدة مقترحات أهمها: إيجاد بديل عن قانون منع الضرب يوضع وفق دراسة جدية تشعر الطالب بجزء من المسؤولية تجاه دراسته وحياته ومدرسته، وفتح مجال للمناقشة مع الطلبة وإعطائهم الثقة. The Research aims at recognizing the opinions of public high school teachers in Lattakia governorate, And determine the difference in their opinions according to many variables as: (Teacher Gender, School Place, Experience and both the Educational and Scientific Qualifications). The Researcher chose a Sample, including 36 teacher of both genders "male and female" work in the Public High School during the school year 2013-2014. And to achieve the purposes of the Research, the Researcher designed a questionnaire. Then , the questionnaire to committee of nine arbitrators in both Damascus and Tishreen University, where the committee proved the questionnaire after it was applied to the group of 30 teachers, then calculating (Alfa Cronbagh), which evaluates in 0.91. The research showed the following results:(The size of the school violence is in the medium magnitude, and the Results showed that there are no important differences between the opinions of teachers of high school in Lattakia about the extent of the school violence there are in schools, according to the following variables:(Teacher Gender, School Place) and that there are important differences according to the following variables(teacher Experience and educational scientific qualification). In Conclusion, the Research included some proposals, the more important of them:( Find a substitute for the Beating Prevention Law, in way aims at making the student bears a part of his responsibility towards his life, study and school, and Open a discussion with students to express their opinions, and give trust to them).